Organic farming: Hope for the sustainable livelihoods of future generations in Pakistan - Abdul Sattar Anjum, Roshan Zada, Waqarul Hassan Tareen (JSSH, 2023)
Organic farming is centuries old human and natural intervention which has been eco-friendly and economically viable. It comprises eco-friendly agricultural techniques leading towards the maximum production without using chemical inputs. Nature friendly farming approach helps in reducing the negative effects of environmental pollution by recycling crop rotation, using crop debris, farm yard manure, pest control with biological methods, appropriate tillage, cultivating legumes to add organic matter in the soil and to mitigate the climate hazards. A majority of rural population in Pakistan is willing to adapt the organic farming practices to save their input costs for better livelihoods. The present component of Pakistan economy is agriculture which contributes 21% to GDP and adds more than 45% labor in agricultural activities. The Pakistani farm-home women are playing a great role in agricultural development and livestock management. Organic farming is efficient for eco-system providing a balance in the life of human, crops and animals; hence leading to the sustainability of the system.